The pan-deacetylase inhibitor panobinostat affects angiogenesis in hepatocellular carcinoma models via modulation of CTGF expression - Gahr, Susanne; Mayr, Christian; Kiesslich, Tobias; Illig, Romana; Neureiter, Daniel; Alinger, Beate; Ganslmayer, Marion; Wissniowski, Till; Di Fazio, Pietro; Montalbano, Roberta; Ficker, Joachim H.; Ocker, Matthias; et al. (International Journal of Oncology, 2015)
Post-translational modifications of chromatin components are significantly involved in the regulation of tumor suppressor gene and oncogene expression. Connective tissue growth factor (CTGF) is an epigenetically regulated growth factor with functions in angiogenesis and cell-matrix interactions and plays a pivotal role in hepatocellular carcinoma (HCC). The pharmacologic inhibition of histone and protein deacetylases represents a new approach to interfere with pathways of apoptosis and angiogenesis. We investigated the effect of the pan-deacetylase inhibitor panobinostat (LBH589) on human HCC cell lines HepG2 (p53wt) and Hep3B (p53null) and in a subcutaneous xenograft model and explored the influence on angiogenesis. Specimens were characterized by quantitative real-time PCR. Protein was separated for western blotting against CTGF, VEGF, VEGF receptor-1 (VEGFR-1/FLT-1), VEGF receptor-2 (VEGFR-2/KDR), MAPK and phospho-MAPK. In vivo, HepG2 cells were xenografted to NMRI mice and treated with daily i.p. injections of 10 mg/kg panobinostat. After 1, 7 and 28 days, real-time PCR was performed. Immunohistochemistry and western blotting were examined after 28 days. An increased significant expression of CTGF was only seen after 24 h treatment with 0.1 µM panobinostat in HepG2 cells and Hep3B cells, whereas after 72 h treatment CTGF expression clearly decreased. In the xenografts, treatment with panobinostat showed a minimal CTGF expression after 1 day and 4 weeks, respectively. In vitro as well as in vivo, VEGF was not affected by panobinostat treatment at any time. In conclusion, panobinostat influences extracellular signaling cascades via CTGF-dependent pathways.
EVALuna2:2025